Juglone Suppresses Inflammation and Oxidative Stress in Colitis Mice - Chen, Shuai; Wu, Xin; Yu, Zengli (Frontiers in Immunology, 2021)
Juglone (JUG), a natural product found in walnut trees and other plants, shows potent antioxidant, antimicrobial, and immunoregulatory activities. However, it remains unknown whether JUG can alleviate ulcerative colitis. This study aims to explore the effect of JUG on dextran sulfate sodium (DSS)-induced colitis in mice. The mice were randomly assigned into three groups: the vehicle group, the DSS group, and the JUG group. The experiments lasted for 17 days; during the experiment, all mice received dimethyl sulfoxide (DMSO, 0.03% v/v)-containing water, while the mice in the JUG group received DMSO-containing water supplemented with JUG (0.04 w/v). Colitis was induced by administering DSS (3% w/v) orally for 10 consecutive days. The results showed that the JUG treatment significantly ameliorated body weight loss and disease activity index and improved the survival probability, colon length, and tissue damage. JUG reversed the DSS-induced up-regulation of proinflammatory cytokines, including interleukin (IL)-6, 12, 21, and 23, and tumor necrosis factor-alpha, and anti-inflammatory cytokines, such as IL-10 and transforming growth factor-beta, in the serum of the colitis mice. Additionally, the activation of mitochondrial uncoupling protein 2 and phospho-Nuclear Factor-kappa B p65 and the inhibition of the kelch-like ECH-associated protein 1 and NF-E2-related factor 2 induced by DSS were also reversed under JUG administration. Although the JUG group possessed a similar microbial community structure as the DSS group, JUG enriched potential beneficial microbes such as Lachnospiraceae_NK4A136_group but not pathogens such as Escherichia Shigella, which was dominative in DSS group, at the genus level. In conclusion, our results demonstrated that JUG could be a promising agent for UC prevention to regulate inflammatory cytokines and oxidative stress.